REALITAS SOSIAL DALAM NOVEL PULANG KARYA LEILA S. CHUDORI: KAJIAN STRUKTURALISME GENETIK - Nurfitriani, Siti (Universitas Pendidikan Indonesia, 2017)
This study aims to determine the social reality in the novel PulangÂ Leila Chudori works were assessed on the basis of genetic structuralism approach. Social reality examined in this study extend short story structure, social structure, and the author's view of the world (world view). The method used in this study is a qualitative method that is supported by the study of genetic structuralism.The results showed that there subfokus social reality in a novel structure Pulang Leila Chudori work, especially in the theme of the story. Social reality contained in the theme in the form of the struggle of the political exiles to return to set foot into the ground water. Events experienced by the characters in the story according to the social aspect that occurs in the political exiles in Indonesia. In addition to the social reality theme also appears in the background, viewpoint, and the characterizations. In the next subfokus realtas society in terms of social structure can be seen that there is a social reality in the novel in accordance with the social structure of which is G30SPKI events, events supersmar, Chinese ethnic cleansing, as well as the May Tragedy. While the authors found subfokus world view through a problematic figure in the story that the author in an interview stated that political eksil an Indonesian citizen who is entitled to a decent living as citizens of Indonesia in general. Based on these results until it can be understood thoroughly and deeply concerning novel Leila Chudori when viewed from the study of genetic structuralism. Research results obtained show that the novel Pulang to contain social reality that can be used as reading material for students and the general public to broaden insight into the history.Keywords: social reality, history, genetic structuralism